Crystalline structures and frustration in a two-component Rydberg gas. (14th December 2015) - Levi, Emanuele; Minář, Jiří; Garrahan, Juan P; Lesanovsky, Igor
Abstract: We study the static behavior of a gas of atoms held in a one-dimensional lattice where two distinct electronically high-lying Rydberg states are simultaneously excited by laser light. We focus on a situation where interactions of van-der-Waals type take place only among atoms that are in the same Rydberg state. We analytically investigate at first the so-called classical limit of vanishing laser driving strength. We show that the system exhibits a surprisingly complex ground state structure with a sequence of compatible to incompatible transitions. The incompatibility between the species leads to mutual frustration, a feature which pertains also in the quantum regime. We perform an analytical and numerical investigation of these features and present an approximative description of the system in terms of a Rokhsar–Kivelson Hamiltonian which permits the analytical understanding of the frustration effects even beyond the classical limit.